ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA BERDASARKAN KRITERIA WATSON - Renza Anjeli (Jurnal Edukasi dan Penelitian Matematika, 2019)
One of the ways to know students’ ability to relate mathematical concept with daily life is by using mathematical word problem. However in reality, students still made mistakes in solving the problems. One of the ways to classify students’ error is by using Watson's criteria which consists of 8 criteria of errors, namely inappropriate data, inappropriate procedure, omitted data, omitted conclusion, response level conflict, undirected manipulation, skills hierarchy problem, above other. Purpose of this research was to analyze the students’ mistake based on Watson's criteria and to find the factors that cause them. This type of research was qualitative research. Data collection techniques used tests and interviews while the analytical techniques was descriptive analysis and data triangulation. The subjects in this research were 32 students of class VIII.10 in SMPN 1 Payakumbuh. The result of this study shows that the most mistakes made by students omitted conclusions with a percentage error of  26.01% because students don’t solve the problem well and because of the carelessness of the students.Keywords - problem based learning model, story problem